IMPLEMENTATION OF E-GOVERNMENT AT THE CENTER FOR TRAINING, DEVELOPMENT AND STUDY OF GOVERNMENT MANAGEMENT INSTITUTIONS (PUSLATBANG KMP LAN) IN MAKASSAR - Nurhazanah, Deafati; Akib, Haedar; Aslinda, Andi (Universitas Negeri Makassar, 2025)
This study aims to determine the Implementation of E-government at the Center for Training and Development and Government Management Studies of State Administration Institutions (PUSLATBANG KMP LAN) in Makassar. This research includes descriptive qualitative research with data collection techniques through observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation and conclusion drawn. The results of the study show that the implementation of E-government at the Center for Training and Development and Management Studies of the State Administration Institution (PUSLATBANG KMP LAN) in Makassar is based on the implementation model of George Edward III, namely: 1) Communication, 2) Resources, 3) Disposition, 4) Bureaucratic structure that in general the implementation of policies is still not good, still needs to be optimized in the Resource indicator so that the impelemmetor can be more optimal in implementing policies This e-government.